Iraq’s neglected humanitarian crisis - Andrew Harper (Forced Migration Review, 2007)
Over three million Iraqis are currently internally displaced or have left Iraq, with possibly one million of these having been displaced since the February 2006 Samarra bombings. Refugees, IDPs and host communities have exhausted their resources. Donors are unresponsive to their needs and governments oblivious to the likely secondary displacement to Europe and further afield.